Mechanical Alloying of Immiscible Metallic Systems: Process, Microstructure, and Mechanism. Issue 4 (1st February 2021) - Shuai, Cijun; He, Chongxian; Peng, Shuping; Qi, Fangwei; Wang, Guoyong; Min, Anjie; Yang, Wenjing; Wang, Weiguo
Abstract : Immiscible metallic systems provide new opportunities for tailoring material properties due to their unique microstructure. However, they are immiscible in the liquid state, or separate into incompatible liquid phase during the cooling process, making it difficult to obtain their alloys or phases. Mechanical alloying is a solid‐state processing route, whose basic principle is to utilize mechanical impact to make materials suffer cyclic deforming, fracturing, and welding. It reduces the energy barrier and provides pathways of atom diffusion, achieving atomic‐level alloying in solid‐state. Notably, mechanical alloying does not undergo the cooling process from liquid to solid phase, which can avoid the solute separation. This article discusses the mechanical alloying process, microstructure, and mechanism of immiscible metallic systems. It focuses on the alloying principles, including solid solutions, intermetallic compounds, nanocrystalline or amorphous alloys. In addition, the effects of process parameters, including rotation speed, milling time, and ball‐to‐powder weight ratio, on microstructure and phase constitution are comprehensively reviewed. Some useful suggestions regarding the preparation of immiscible metallic systems are also put forward for future works. Abstract : This article discusses the mechanical alloying process, microstructure, and mechanism of immiscible metallic systems. It focuses on the alloying principles, including solid solutions, intermetallic compounds, nanocrystalline or amorphous alloys. The effects of process parameters on microstructure and phase constitution are comprehensively reviewed. Some useful suggestions regarding the preparation of immiscible metallic systems are also put forward for future works.